The Gender Pay Gap in EU Countries – New Evidence Based on EU-SES 2014 Data - Christina Boll; Andreas Lagemann (Intereconomics, 2019)
Gender differences in wages are a persistent pattern in most European countries. This study analyses the earnings divide between men and women and the driving forces behind it in 26 countries. In 2014, the cross-country gender pay gap stood at 14.2%. However, country-level results differ tremendously with high gaps of more than 20% in Estonia and Germany and gaps below 5% in Belgium, Luxembourg, Slovenia and Romania. While part of the earnings divide can be explained by gendered sector affi liation and the high share of atypical employment among women, a large portion of the gender pay gap remains unexplained by the data. Even though the gender pay gap statistics are unable to identify the (non-)existence of discrimination, it still calls for diverse measures both at the state and the firm level.
Keywords: 330